Application of different methods for cervical cancer detection - Zhou, Xingyu (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Cervical cancer remains a widespread and challenging malignancy that affects women worldwide and poses significant clinical and public health issues. Since it is difficult to find early cervical lesions in the patient’s own state, it is very important to apply appropriate and effective detection and screening for cervical cancer and precancerous lesions. This research investigates the development of cervical cancer and the various subtypes of HPV, which are the primary cause of cervical lesions. Combined with the investigation of the three most common clinical screening methods, including liquid-based thin-layer cell assay (TCT), human papillomavirus detection (HPV) and colposcopy detection operating methods and screening standards, data were used to comprehensively analyze the accuracy, sensitivity and specificity of single or combined screening of the three detection methods. This research examines various methods and technologies for cervical cancer screening, with the goal of determining their clinical effectiveness in detecting cervical lesions. Based on screening data, the results are positive and the methods are deemed suitable for early diagnosis of the condition. It is recommended that these screening tools be utilized in a clinical setting.